2012
DOI: 10.1080/14786419.2011.561799
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of eugenol on glucan is essential for the biofilm eradication effect on caries-related biofilm in an artificial mouth model

Abstract: This study aimed to evaluate the inhibitory effects of herbal extracts on caries-related bacteria, glucan and biofilm in vitro. Sensitive tests of bacteria were carried out by broth dilution method on a 96-microwell plate. Glucan inhibition tests were carried out using the phenol sulphate method. A minimum biofilm inhibitory concentration (MBIC) test was performed in an artificial mouth model. The results of the MBIC of agents were 8, 16 and 32 mg mL(-1) for eugenol, tannic acid and magnolol, respectively. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The results showed that the formation of water-insoluble glucans by S. mutans was significantly suppressed in the presence of eugenol. Our results correlate well with other reports that eugenol suppresses the insoluble and soluble glucan synthesis of S. sobrinus (8,18). S. mutans synthesizes glucans from sucrose by the action of Gtfs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that the formation of water-insoluble glucans by S. mutans was significantly suppressed in the presence of eugenol. Our results correlate well with other reports that eugenol suppresses the insoluble and soluble glucan synthesis of S. sobrinus (8,18). S. mutans synthesizes glucans from sucrose by the action of Gtfs.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study indicated that eugenol may be an ideal natural agent for use in oral care products. Eugenol inhibits the growth and insoluble and soluble glucan synthesis of S. sobrinus (8). However, the therapeutic effect of eugenol against dental caries has not been thoroughly evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, natural antibacterial compounds in particular plant-derived compounds, are attracting attention to develop novel therapeutics against oral infectious diseases ( Allaker & Douglas, 2009 ; Borges et al, 2016 ). Eugenol is a good example of natural compounds widely used in dental care as an antimicrobial, analgesic and anti-inflammatory, showing to be active against caries-related oral bacteria ( Jadhav et al, 2004 ; Li et al, 2012 ; Xu et al, 2013 ). These plant-derived natural compounds, also referred as phytochemicals, are responsible for plant interactions with the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The effect in vitro of eugenol on the cariogenic properties of S. mutans was demonstrated previously by Xu et al (2013). Eugenol inhibited, significantly, the acid production from carbohydrate fermentation, and, as well as, the synthesis of water-insoluble glucans through glucosyltransferases (Gtf) of S. mutans inhibition (Li et al, 2012). Similar results were obtained using artificial mouth models with oral bacteria of the genus Streptococcus, wherein eugenol was able to eradicate S. mutans and S. sobrinus biofilms by inhibiting the synthesis of insoluble and soluble glucans (Xiao and Koo, 2010).…”
Section: Discussionmentioning
confidence: 59%
“…The biosynthesis of water-insoluble glucans through glucosyltransferase (Gtf) is an essential Streptococcal mechanism for the adhesion, co-adhesion and bacterial accumulation on the tooth surface, in addition to providing structural integrity for the biofilm matrix (Li et al, 2012). Similarly, there are specific water-insoluble glucans that promote the adhesive interactions of bacteria with solid surfaces, and inhibition of Gtf activity (particularly GtfC and GtfB) and polysaccharide synthesis is an approach to prevent biofilm-related diseases (Abachi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%